Odpowiedzi

2009-10-07T20:42:26+02:00
B) 2√3+ √27/ 5√3 = 2√3+3√3/5√3 = 5√3/5√3 = 1 <rozłożyłam √27 na czynniki>
d) 2/ √2 - 1 = 2√2-1 <pomnożyłam przez √2-1>
f) 2√3- 1/ 2-√3 = 2*3-1/2-3=6-1/-1=5/-1=-5 <pomnożyłam całość przez √3>
h) 5√6 / √3 + √2=(5√18)/(3+√2)=(5√36)/(3+2)=5*6/5=30/5=6
<pomnożyłam najpierw przez √3 później przez √2>
2009-10-07T21:02:26+02:00
B 2√3+ √27/ 5√3 = 2 √3 +√9x3 / 5√3 =2 √3+ 3√3 /5√3 =2 √3+ 3/5= 13/5 √3

d) 2/ √2 - 1 =2/1,44 - 1 =1,38-1 = 0,38

f) 2√3- 1/ 2-√3 =2√3- 1/2-1,73=2√3- 3,70 = -1,70√3

h) 5√6 / √3 + √2 =12,25/1,44 +1,44= 8,51+ 1,44= 9,95